EXISTENCE OF PROCEDURES TO EVALUATE INTANGIBLE BENEFITS OF ICT INVESTMENTS. PERCEPTUAL PERSPECTIVE OF EMPLOYEES OF NICARAGUAN COMPANIES. - Lindo González, O.D. (Nexo Revista Científica, 2017)
Investments in Information and Communication Technologies (ICTs) provide companies with important benefits, but it is considered that the existing procedures for their evaluation do not take into account intangible benefits. In this study we deal with this assumption by analyzing information gathered with a questionnaire applied on-line from the perceptual perspective of active employees of companies based in Nicaragua in private and public sectors on the existence of procedures to evaluate benefits obtained from this kind of projects in their organizations. We created two profiles: one of the employees polled and one of the companies they worked for. We also estimated the weight that according with those polled the evaluation of said benefits has in their companies. The analysis of these profiles and of the estimated weight allowed us to conclude that there exists a split perception of employees on the existence of procedures to evaluate ICT investments in their companies: one part perceived that such procedures exist and take into account tangible and intangible benefits; another part perceived that the evaluation of intangible benefits is important, but their companies do not have procedures therefor.